Aroma Therapy Influence to the Morning Sickness on the First Trimester Pregnant Women in BPM Waru and Menanggal - Anggasari, Yasi (Journal of Global Research in Public Health, 2018)
Emesis gravidarum is a common or often symptom of first trimester pregnancy, the symptoms may be caused due to increased levels of the hormone estrogen and Human Chorionic Gonodotropin. Nausea usually occurs in the morning, but there are arising every time and night. These symptoms usually occur six weeks after the first day of the last menstrual period lasting approximately 10 weeks. The purpose of this study The purpose of this research is to know the influence of aroma therapy on decreased emesis gravidarum in first trimester pregnant women in BPM Waru dan Menanggal. Research design using Pre-Experimental with cross sectional approach. The population is all pregnant women in the first trimester who experience emesis gravidarum in BPM Waru dan Menunggal for 30 patients, a large sample of 28 respondents taken with simple random sampling technique. Variable independent is giving aroma therapy and dependent variable is emesis gravidarum in pregnant mother. The research instrument used questionnaire. Data were analyzed with Wilcoxon Signed Rank statistic test with significance level (Î± = 0,05). The results of the study of 28 respondents were almost 21 (85.7%) of respondents before giving aromatherapy with severe gravidarum emesis, and after administration of aroma therapy, most of them had mild degree gravidarum emesis. Wilcoxon Signed Rank test results Ï = 0.000 <Î± then H0 rejecte, meaning Aroma Therapy Affects Against Gravidarum Emesis In First Trimester Pregnant Women at BPM Waru dan Menanggal. The results showed that after done Aroma Therapy of 28 respondents, most (75%) respondents said comfortable, it means that the technique of aroma therapy has an effect on the emission of emesis gravidarum